Early Humoral Responses of Hemodialysis Patients after COVID-19 Vaccination with BNT162b2. Issue 7 (July 2021) - Speer, Claudius; Göth, Daniel; Benning, Louise; Buylaert, Mirabel; Schaier, Matthias; Grenz, Julia; Nusshag, Christian; Kälble, Florian; Kreysing, Martin; Reichel, Paula; Töllner, Maximilian; Hidmark, Asa; et al.
Visual Abstract: Abstract : Background and objectives: Patients receiving hemodialysis are at high risk for both severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection and severe coronavirus disease 2019. A lifesaving vaccine is available, but sensitivity to vaccines is generally lower in patients on dialysis. Little is yet known about antibody responses after coronavirus disease 2019 (COVID-19) vaccination in this vulnerable group. Design, setting, participants, and measurements: In this prospective single-center study, we included 22 patients on dialysis and 46 healthy controls from Heidelberg University Hospital between December 2020 and February 2021. We measured anti-S1 IgG with a threshold index for detection greater than one, neutralizing antibodies with a threshold for viral neutralization of ≥30%, and antibodies against different SARS-CoV2 fragments 17–22 days after the first dose and 18–22 days after the second dose of the mRNA vaccine BNT162b2. Results: After the first vaccine dose, four of 22 (18%) patients on dialysis compared with 43 of 46 (93%) healthy controls developed positive anti-S1 IgG, with a median anti-S1 IgG index of 0.2 (interquartile range, 0.1–0.7) compared with nine (interquartile range, 4–16), respectively. SARS-CoV2 neutralizing antibodies exceeded the threshold for neutralization in four of 22 (18%) patients on dialysis compared with 43 of 46 (93%) healthy controls, with a median percent inhibition of 11 (interquartile range, 3–24) compared with 65 (interquartile range, 49–75), respectively. After the second dose, 14 of 17 (82%) patients on dialysis developed neutralizing antibodies exceeding the threshold for viral neutralization and antibodies against the receptor binding S1 domain of the spike protein, compared with 46 of 46 (100%) healthy controls, respectively. The median percent inhibition was 51 (interquartile range, 32–86) compared with 98 (interquartile range, 97–98) in healthy controls. Conclusions: Patients receiving long-term hemodialysis show a reduced antibody response to the first and second doses of the mRNA vaccine BNT162b2. The majority (82%) develop neutralizing antibodies after the second dose but at lower levels than healthy controls.